A SIMPLE TLC METHOD FOR EVALUATION OF NICOTINE IN CIGARETTES - HOSU, Anamaria; CIMPOIU, Claudia (Studia Universitatis Babeș-Bolyai Chemia, 2015)
In this study, a rapid and sensitive thin-layer chromatographic method for evaluation of nicotine content in twelve popular cigarettes from Romanian market has been used. The TLC separation was performed on silica gel F254 plates using a mixture of ethyl acetate - methanol - conc. ammonia - water 80:25:0.2:15.8, v/v/v/v as mobile phase. Detection was made in UV light at 254nm and in visible light after derivatization with Dragendorff’s reagent and the areas of the characteristic bands of nicotine were determined using ImageJ software. The results showed a significant variation of nicotine content in investigated cigarettes, but in good agreement with the concentrations of nicotine specified on the label.